On the intrinsic hardness of a metallic film/substrate system: Indentation size and substrate effects - Ma, Z.; Zhou, Y.; Long, S.; Lu, Chunsheng (ELSEVIER, 2012)
To examine effects of indentation size and substrate on the hardness determination of thin films, two typical types of hard film/soft substrate (Ni/Fe) and soft film/hard substrate (Al/Si and Al/glass) systems are investigated. A simple model is proposed to predict the intrinsic hardness of thin films, which allows a more accurate fitting to empirical data and the estimation of ultimate film hardness. The model can be used to interpret indentation data and extrapolate the indentation depth-hardness curve to an important region where indentation depth lies between 1% to 5 times of film thickness. The results are well consistent with the evolving trend of composite hardness obtained from experiments and numerical results by finite element analysis.